Pigmentos fotossintéticos em clones de seringueira sob ataque de oídio - Gonzalez, Gisely Cristina [UNESP] (2013)
The rubber tree [Hevea brasiliensis (Willd. ex Adr. Of Juss.) Muell. Arg.] can be affected by the occurrence of the fungus Oidium heveae, which causes one of the most important diseases of rubber trees, powdery mildew. This work meet changes in photosynthetic pigments, an indicator of oxidative stress, in seedlings of three Hevea brasiliensis clones, RRIM 600, GT1 and PR255, under infection in Oidium heveae. The experiment was conducted in an open environment under natural photoperiod conditions and at the beginning of the trial, the rubber plants that would be inoculated were sprayed with an aqueous suspension containing Oidium heveae at a concentration of 16 x 104conidia mL-1. On the day of inoculation and after 48, 96, 144 and 192 h leaf samples were collected for the determination of photosynthetic pigments. Degradation in photosynthetic pigments in the period of infection was observed in rubber tree clones studied; thus, there is oxidative stress in clones of rubber trees. No promising genetic material for genetic improvement work stress tolerance by Oidium heveae was identified.